Effect of reinforcement size on the concrete / reinforcement bond strength - Turk, K.; Yildirim, M.S.; Caliskan, S. (Thomas Telford Services Ltd, 2003)
Bond strength between reduced-water-content concrete and tensile reinforcement in spliced mode has been investigated. Three different diameters (12, 16 and 22mm) of tensile steel were spliced in the constant moment zone, where the load was applied to, in geometrically identical nine beams. An empirical equation has been derived to calculate the bond strength. It is found that there is a considerable size effect in the experimental results, i.e. as the diameter of the reinforcement reduces the bond strength and the ductility increases significantly, whilst the stiffness of the beams reduces.
Role of Cement Science in Sustainable Development - International Symposium Celebrating Concrete: People and Practice -- 3 September 2003 through 4 September 2003 -- Dundee -- 66795
Keywords: Bond strength; Size effect; Splice length; Tensile reinforcement